Faktor yang Berhubungan dengan Penerimaan Alat Kontrasepsi Dalam Rahim Pascasalin di Samarinda - Prima Derry Pella Todungbua'; Ratnasari Dwi Cahyanti; Supriyadi Hari Respati (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Maternal mortality rate (MMR) in Indonesia is 305 per 100.000 live births. The intervention to suppress MMR according to four pillars of Safe Motherhood is reducing the possibility of woman becoming pregnant with Family Planning. The postpartum period is an important time to start, but underutilized. All contraceptive methods may be used, but the high rate of drop-out in non-long-term methods, counselling is directed to long-term methods like IUD.Objective: To determine factor that related postpartum IUD acceptance in Samarinda.Method: The research method is observational with cross sectional design. Sampling is done by purposive sampling. Data were obtained through questionnaire.Result: There was no significant association between age (p=0.438), parity (RR=0.7; p=0.077), education (RR=1.11; p=0.611), and income (RR=0.69; p=0.105) with acceptance of postpartum IUD. Employment (RR=1.64; p=0.025), history of family planning counselling (RR=3.37; p<0.001), and husband's approval (RR=28.8; p=<0.001) have significant association with the acceptance of postpartum IUD.Conclusion: Age, parity, education, and income are not related factors of postpartum IUD acceptance, while employment, husband's approval, and history of family planning counselling are related factors of postpartum IUD acceptance in Samarinda.Keywords: Postpartum IUD, family planning counselling, husband's approval.